The performance of semi-empirical Bayesian control charts for monitoring Weibull data. Issue 1 (2nd January 2018) - Erto, Pasquale; Pallotta, Giuliana; Palumbo, Biagio; Mastrangelo, Christina M.
Abstract: In this paper we investigate the performance of semi-empirical Bayesian control charts to monitor the percentiles and the shape parameter of a Weibull distribution. These charts have been recently introduced in literature, where it is shown how Weibull-distributed data need specifically designed control schemes and how a Bayesian approach can help in such cases. The main focus of this paper, instead, is a simulation study of the charts' performance. To this aim, a large Monte Carlo analysis is presented, highlighting the main effects on the chart performance of single/combined changes in the Weibull parameters. Some Weibull contour plots are presented to visualize the investigated technological scenarios. An illustrative example using a reference data-set is included too.